Reovirus Protein ςNS Binds in Multiple Copies to Single-Stranded RNA and Shares Properties with Single-Stranded DNA Binding Proteins - Gillian, Anne Lynn (American Society for Microbiology, 2000)
Reovirus nonstructural protein ςNS interacts with reovirus plus-strand RNAs in infected cells, but little is known about the nature of those interactions or their roles in viral replication. In this study, a recombinant form of ςNS was analyzed for in vitro binding to nucleic acids using gel mobility shift assays. Multiple units of ςNS bound to single-stranded RNA molecules with positive cooperativity and with each unit covering about 25 nucleotides at saturation. The ςNS protein did not bind preferentially to reovirus RNA over nonreovirus RNA in competition experiments but did bind preferentially to single-stranded over double-stranded nucleic acids and with a slight preference for RNA over DNA. In addition, ςNS bound to single-stranded RNA to which a 19-base DNA oligonucleotide was hybridized at either end or near the middle. When present in saturative amounts, ςNS displaced this oligonucleotide from the partial duplex. The strand displacement activity did not require ATP hydrolysis and was inhibited by MgCl(2), distinguishing it from a classical ATP-dependent helicase. These properties of ςNS are similar to those of single-stranded DNA binding proteins that are known to participate in genomic DNA replication, suggesting a related role for ςNS in replication of the reovirus RNA genome.